Implementasi Agile Scrum Pembuatan Game Visual Novel Cerita Asal Usul Kota Surabaya - Artiarini Kusuma Nurindiyani; Ashafidz Fauzan Dianta; Halimatus Sa’dyah; Ilham Agung Riyadi (Puslitbang Sekawan Institute Nusa Tenggara, 2023)
Surabaya is the second largest city in Indonesia after Jakarta. The city of Surabaya has a distinctive designation, namely